Holism of Islamic Education: A Comprehensive Review of the Management of the Ibnu Abbas Islamic Boarding School in Klaten, Central Java - Qiyadah Robbaniyah; Diningrum Citraningsih; Roidah Lina (At-Tarbiyat, 2024)
Islamic boarding schools in Indonesia play an important role in developing Islamic education, but views on them are limited. Islamic education includes more than just the transfer of knowledge, but also values in the teaching and learning process, such as tarbiyah and ta'dib. Islamic boarding schools also contribute to improving the quality of human resources. This study aims to explore the Holism of Islamic Education: A Comprehensive Review of the Management of the Ibnu Abbas Klaten Islamic Boarding School in Central Java. The research method used is descriptive qualitative research, by means of observation, interviews and documentation. The result of this research is the management of Islamic education in the Ibn Abbas Klaten Islamic boarding school, various aspects of management such as leadership, public relations, finance, infrastructure, and dormitory are described in detail. Through a holistic approach, this Islamic boarding school divides its organizational structure into three main units: education, human resources, and finance, with an emphasis on friendship and consensus deliberation. Excellence programs in public relations and media management, especially through IBBASTV's YouTube channel, demonstrate the commitment of Islamic boarding schools in service to the surrounding community. This holistic approach in education management in Islamic boarding schools includes not only academic aspects, but also aspects of cleanliness, safety, comfort, and self-development of students. Various programs and activities are set to support the vision and mission of holistic education, including the use of modern communication technologies such as WhatsApp to improve communication and coordination between stakeholders. In maintaining cleanliness and availability of complete infrastructure, Islamic boarding schools affirm their commitment to providing a holistic and sustainable educational environment.